The selective battery of motor tests for a track and field event long jump - Idrizovic, K.; Nicin, D. (Sports Science and Health, 2014)
The basic goal of this study was identification of the selection battery of motor tests for long jump. In this way, coaches would be enabled in the future to determine their competitive potentials more simply, and to direct the organisation of a training process more precisely. The sample of the examinees for this research composed of 1200 boys from primary and secondary schools. The basic sample was divided into eight subsamples with 150 boys from the fifth class of primary school (12 years ± 6 months) to the fourth class of secondary school (18 years ± 6 months). The area of the motor indicators, on the basis of which it should be determined the selection battery, was structured from the indicators of those motor abilities, that were decisive for the quality result in long jump (speed, explosive strength of upper extremities, explosive strength of lower extremities and flexibility). This research proved that the biggest level of selective quality, is related to the tests for the estimation of explosive strength of lower extremities: vertical jump test and standing triple jump, tests for the estimation of running speed: running 20 m flying start and running 30 m standing start, and test for the estimation of explosive strength of upper extremities, lying medicine ball throw. These are tests which must be in each battery of tests which, as a aim, has the talent identification of young jumpers for long jump.